Spiritual Contradiction Scale: A New Way of Understanding Internal and External Contradictions - Okan, Nesrullah; Köse, Nihat; Kardaş, Selami (Springer, 2024)
The Spiritual Contradiction Scale was developed to quantify spiritual contradictions experienced by individuals. The scale was developed following a literature review and online interviews conducted with 72 individuals who reported contradictory experiences. Based on the interviewees’ statements, candidate items were identified and presented to experts for review. Twenty-five items were generated and reviewed by three experts. These items were subject to exploratory factor analysis (n = 265), and then to confirmatory factor analysis (n = 186). Criterion validity was examined in a third sample (n = 70). Following the analyses, it was concluded that the Spiritual Contradiction Scale is comprised of two dimensions and 12 items (Internal Contradiction items = 8; External Contradiction = 4 items). The scale aims to convey information about the inconsistency between individuals’ spiritual beliefs, values, and actions. To ascertain the scale’s validity and reliability, exploratory factor analysis, confirmatory factor analysis, and criterion validity analyses were carried out. The exploratory factor analysis revealed a 12-item structure divided into two dimensions. The Spiritual Contradiction Scale can be helpful for individuals to recognize and manage their spiritual contradictions, especially in counseling and therapy processes. In addition, conducting further studies utilizing the scale across different cultures and age groups could yield greater insight into spiritual incongruity. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2023.
Keywords: Reliability; Scale development; Spiritual contradiction; Validity